2018
DOI: 10.1016/j.ihj.2018.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac resynchronization therapy is associated with improvement in clinical outcomes in Indian heart failure patients: Results of a large, long-term observational study

Abstract: BackgroundHeart failure (HF) is a common health problem in South Asia, and its incidence and prevalence are projected to rise. Cardiac resynchronization therapy (CRT) has been shown to improve mortality, reduce hospitalizations, and improve symptoms in selected patients with HF. The South Asian Systolic Heart Failure Registry (SASHFR) was designed to be a large and comprehensive registry of Indian HF patients with the purpose of enhancing the quality of care and clinical outcomes of HF patients by promoting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…In a study conducted by Naik et al in India, it was found that CRT treatment shows a significant improvement in the clinical conditions of the patients compared to other pharmacological interventions. 9 Particularly, the dyssynchrony parameters including SPWMD, LVEMD and IVD significantly improved after CRTD implantation.…”
Section: Discussionmentioning
confidence: 92%
“…In a study conducted by Naik et al in India, it was found that CRT treatment shows a significant improvement in the clinical conditions of the patients compared to other pharmacological interventions. 9 Particularly, the dyssynchrony parameters including SPWMD, LVEMD and IVD significantly improved after CRTD implantation.…”
Section: Discussionmentioning
confidence: 92%
“…In a large, long-term observational study of Indian heart failure patients, out of 471 enrolled patients only 24.6% opted for cardiac resynchronization therapy–pacemaker/CRT-D; in the remaining 75.4% of patients, financial constraints were the main reason for therapy refusal. 8 With conduction system pacing providing complete correction of wide QRS, LBBP would obviate the need for CS lead placement. The additional cost, procedural duration, poor venous anatomy, phrenic nerve capture, high capture threshold, and lead dislodgments associated with CS lead placement could be addressed by complete correction of conduction system disease by LBBP.…”
Section: Discussionmentioning
confidence: 99%
“…There has been some evidence to suggest that there is a weak correlation between electrical and mechanical dyssynchrony inpredicting subsequent benefit of CRT. 2 One third of patients with prolonged QRS do not exhibit intra-left ventricular (LV) dyssynchrony, 1 , 2 , 3 which may explain reasons for non-response. This study evaluates baseline echocardiographic parameters of dyssynchrony in patients undergoing CRT implantation and their evolution after CRT on follow up.…”
Section: Introductionmentioning
confidence: 99%